2022
DOI: 10.1093/fampra/cmac100
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of dropout and compliance of children participating in a multidisciplinary intervention programme for overweight and obesity in socially deprived areas

Abstract: Background Children with overweight and obesity in socially deprived areas (SDAs) are less likely to complete and be compliant to a weight-loss programme. Objectives To identify factors associated with dropout and compliance of a multidisciplinary weight-loss programme in SDA. Methods This prospective longitudinal cohort study included children (6–12 years) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In a prospective longitudinal cohort study of children with overweight and obesity in socially deprived areas of Rotterdam, Hassan et al [14] demonstrated a dropout rate of 33.9%. Children with overweight parents had a significantly lower probability of dropout than those with parents with obesity or normal weight.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a prospective longitudinal cohort study of children with overweight and obesity in socially deprived areas of Rotterdam, Hassan et al [14] demonstrated a dropout rate of 33.9%. Children with overweight parents had a significantly lower probability of dropout than those with parents with obesity or normal weight.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to speculate that normal-weight parents worry less about weight, so they may not evaluate the urgency of losing weight. Instead, the higher risk of dropout found in the group of children with parents with obesity could be correlated with the notion that necessary lifestyle changes might be more complicated for them [14,39]. Park et al [15] identified lower family functioning, lower initial attendance rates, and non-self-directed pathways as factors associated with dropout.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation